Hubungan Antara Gaya Pembelajaran Dengan Jantina dan Pencapaian Akademik Dalam Kalangan Pelajar Tahun Tiga Sarjana Muda Pendidikan, Universiti Utara Malaysia, Kedah: Satu Kajian Kes - Farawahida, Shahruddin (2011)
The purposes of this study are to identify the relationship between learning styles with gender and academic achievement among third year student’s Bachelor of Education at University Utara Malaysia, Kedah. The learning styles were based on Entwistle which includes Deep Approach, Surface Approach and Strategic Approach. The instrument for this research is an Approaches and Study Skills Inventory for Students (ASSIST) based on Entwistle's Model of Learning Styles. The samples of this study are comprised 170 students whose are third year students, Bachelor of Education, UUM. This selection was done by using independent random sampling. The SPSS software was used to perform the statistical analysis required descriptive statistics for demographic factors, including the respondent mean, percentages, and standard deviation and inferential statistics for the Independent Sample t-test and Correlation. The analysis result indicated that the highest learning style practiced by the students is the Strategic Approach (M = 4:02, SD = 0:32) followed by Deep Approach (M = 3.97, SD = 0.26), and the lowest is Surface Approach (M = 3.33, SD = 0.49). The findings also indicated that there are no significant differences between Deep Approaches (t (170) = -1.89, p = 0.060) and Surface Approaches (t (170) = 1.96, p = 0052) across gender accept the Strategic Approach (t (170) = -3.12, p = 0.002) where female students (M = 4:06, SD = 0:32) are more applied this style compare with male students (M = 3.87, 00:27). Further, the findings of correlation analysis showed that academic achievement is not significantly correlated with the three learning approaches (Deep, Surface and Strategic). However, these findings shows that there are positively significant relationship between Deep Approach (r = 0.63, p = 0.00) and Strategic Approach. As a result, only Strategic Approach is showing difference across gender but all of these styles are not related to academic achievement. Based on these findings, further researches are suggested to enhance the knowledge and helping students to more understanding the importance of learning style that they were applied.